2013
DOI: 10.1007/s10208-013-9162-z
|View full text |Cite
|
Sign up to set email alerts
|

Solving Quadratic Equations via PhaseLift When There Are About as Many Equations as Unknowns

Abstract: This note shows that we can recover any complex vector x 0 ∈ C n exactly from on the order of n quadratic equations of the form | a i , x 0 | 2 = b i , i = 1, . . . , m, by using a semidefinite program known as PhaseLift. This improves upon earlier bounds in [3], which required the number of equations to be at least on the order of n log n. Further, we show that exact recovery holds for all input vectors simultaneously, and also demonstrate optimal recovery results from noisy quadratic measurements; these resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
388
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(403 citation statements)
references
References 6 publications
14
388
1
Order By: Relevance
“…In a separate paper, [14], the authors developed further a similar algorithm in the case of windowed DFT. The original requirement of m = O(n log(n)) vectors has been relaxed to m = O(n) in [15]. Similar convex optimization solutions have been proposed by the authors of [20] and [34].…”
Section: Introductionmentioning
confidence: 99%
“…In a separate paper, [14], the authors developed further a similar algorithm in the case of windowed DFT. The original requirement of m = O(n log(n)) vectors has been relaxed to m = O(n) in [15]. Similar convex optimization solutions have been proposed by the authors of [20] and [34].…”
Section: Introductionmentioning
confidence: 99%
“…The first convex relaxation of the phase retrieval problem has been introduced by Candes et al [12]- [14]. He observed that the non-convex measurements y on vectors x become linear measurements on matrices X = xx H where (.)…”
Section: A Phaseliftmentioning
confidence: 99%
“…The equalities in (5) no longer hold in presence of noise. The following formulation has then been proposed in [14]:…”
Section: A Phaseliftmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, there are two main categories of phase retrieval approaches in existing approaches, namely, semi-definite programming-based (SDP-based) approaches [7][8][9][10][11] and iterative projection approaches (Fienup-type methods) [12][13][14][15][16][17][18]. SDP-based approaches are not suitable for largescale problems, so we do not discuss them in the paper.…”
Section: Introductionmentioning
confidence: 99%